Epitope mapping of PfCP-2.9, an asexual blood-stage vaccine candidate of Plasmodium falciparum - He Zhicheng; Zhang Dongmei; Wu Yuan; Wang Rui; Li Changling; Pan Weiqing (Malaria Journal, 2010)
Abstract Background Apical membrane antigen 1 (AMA-1) and merozoite surface protein 1 (MSP1) of Plasmodium falciparum are two leading blood-stage malaria vaccine candidates. A P. falciparum chimeric protein 2.9 (PfCP-2.9) has been constructed as a vaccine candidate, by fusing AMA-1 domain III (AMA-1 (III)) with a C-terminal 19 kDa fragment of MSP1 (MSP1-19) via a 28-mer peptide hinge. PfCP-2.9 was highly immunogenic in animal studies, and antibodies elicited by the PfCP-2.9 highly inhibited parasite growth in vitro. This study focused on locating the distribution of epitopes on PfCP-2.9. Methods A panel of anti-PfCP-2.9 monoclonal antibodies (mAbs) were produced and their properties were examined by Western blot as well as in vitro growth inhibition assay (GIA). In addition, a series of PfCP-2.9 mutants containing single amino acid substitution were produced in Pichia pastoris. Interaction of the mAbs with the PfCP-2.9 mutants was measured by both Western blot and enzyme-linked immunosorbent assay (ELISA). Results Twelve mAbs recognizing PfCP-2.9 chimeric protein were produced. Of them, eight mAbs recognized conformational epitopes and six mAbs showed various levels of inhibitory activities on parasite growth in vitro. In addition, seventeen PfCP-2.9 mutants with single amino acid substitution were produced in Pichia pastoris for interaction with mAbs. Reduced binding of an inhibitory mAb (mAb7G), was observed in three mutants including M62 (Phe491→Ala), M82 (Glu511→Gln) and M84 (Arg513→Lys), suggesting that these amino acid substitutions are critical to the epitope corresponding to mAb7G. The binding of two non-inhibitory mAbs (mAbG11.12 and mAbW9.10) was also reduced in the mutants of either M62 or M82. The substitution of Leu31 to Arg resulted in completely abolishing the binding of mAb1E1 (a blocking antibody) to M176 mutant, suggesting that the Leu residue at this position plays a crucial role in the formation of the epitope. In addition, the Asn15 residue may also play an important role in the global folding of PfCP-2.9, as its substitution by Arg lead to reduced binding of most mAbs and abolishing the binding of mAb6G and mAbP5-W12. Conclusions This study provided valuable information on epitopes of PfCP-2.9 vaccine candidate through generation of a panel of mAbs and a series of PfCP-2.9 mutants. The information may prove to be useful for designing more effective malaria vaccines against blood-stage parasites.